2016
DOI: 10.1371/journal.pgen.1006425
|View full text |Cite|
|
Sign up to set email alerts
|

Pleiotropic Mechanisms Indicated for Sex Differences in Autism

Abstract: Sexual dimorphism in common disease is pervasive, including a dramatic male preponderance in autism spectrum disorders (ASDs). Potential genetic explanations include a liability threshold model requiring increased polymorphism risk in females, sex-limited X-chromosome contribution, gene-environment interaction driven by differences in hormonal milieu, risk influenced by genes sex-differentially expressed in early brain development, or contribution from general mechanisms of sexual dimorphism shared with second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 88 publications
9
74
1
3
Order By: Relevance
“…[124]. First, SNPs were filtered using PLINK[63,64] (see web resources) for Hardy-Weinberg equilibrium (HWE), call rate, minor allele frequency (MAF) and Mendel errors separately in each ASD dataset (S6 Table).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[124]. First, SNPs were filtered using PLINK[63,64] (see web resources) for Hardy-Weinberg equilibrium (HWE), call rate, minor allele frequency (MAF) and Mendel errors separately in each ASD dataset (S6 Table).…”
Section: Methodsmentioning
confidence: 99%
“…[124]. For each dataset, the following individual quality control filters were applied using PLINK[63,64]: genotyping rate, heterozygosity rate, verifying individual sex, verifying known relationships, removing individuals contributing to confounding relationship, and keeping one instance of individuals present in multiple studies.…”
Section: Methodsmentioning
confidence: 99%
“…Intra-locus sexual conflict is the result of selection acting in divergent directions on male and female phenotypes that are underpinned by a shared genetic architecture 7 . However, both forward 46 and reverse 47,48,83,84 genetic studies have indicated that the genetic architecture underlying many traits expressed in both sexes can differ substantially between females and males. In theory, sex-specific genetic architecture, where an allele affects one sex but not the other, resolves contradictory selection pressures 45,46 and relaxes balancing selection.…”
Section: Clarifying the Role Of Sexual Conflict In Evolutionmentioning
confidence: 99%
“…Aunque la explicación exacta para este fenómeno no se conoce, se ha visto que las variantes genéticas que regularían rasgos antropométricos y polimorfismos en el cromosoma X darían cuenta de esta diferencia 22 . Por otra parte, aunque no encontramos una clara asociación, existe una tendencia a detectarse un mayor porcentaje de casos con CMA positivo si fueron derivados con CD.…”
Section: Discussionunclassified